Crowding and Territoriality within Urban Safety (Case Study: Ketabang, Surabaya, Indonesia) - Fery Asta Wibowo; Dewi Septanti; Haryo Sulistyarso (Jurnal Teknik ITS, 2019)
The city of Surabaya is one of the largest metropolitan cities in Indonesia with positive city growth and development. Along with this, the wave of urbanization and the increase in safety threats also increased. The increased threats triggered the procurement of facilities related to high safety. However, Ketabang, as one of the regions that have the availability of complete safety facilities, still has a great record of safety threats, especially in public space. Thus, an evaluation of the effectiveness of the facility needs to be carried out, especially on the topic of controlling the crowd and clear territorial boundaries. The control itself is related to the limitation of public activities, which can be one of the factors that cause reduced awareness and surveillance of the perpetrators of safety threats. Because of it, this region needs further research on each level of territorial crowds and territorial boundaries that can affect safety in public spaces. This study uses qualitative data analysis, character appraisal of related facilities, and cognitive mapping as a research method. The results of the analysis process outline the influence of crowds and territorial boundary on the safety of users of public spaces in the study area. These results are the main handle in providing an evaluation of the design and provision of facilities that can improve the safety of public space users.